1999
DOI: 10.1038/sj.onc.1203155
|View full text |Cite
|
Sign up to set email alerts
|

Fusion of the RBP56 and CHN genes in extraskeletal myxoid chondrosarcomas with translocation t(9;17)(q22;q11)

Abstract: Although most extraskeletal myxoid chondrosarcomas (EMC) are cytogenetically characterized by the translocation t(9;22)(q22;q12), another subset has recently been identi®ed carrying a t(9;17)(q22;q11). Whereas the t(9;22) is known to result in fusion of the CHN (TEC) gene from 9q22 with the EWS gene from 22q12, creating a chimeric EWS/CHN, the genes involved in the t(9;17) of EMC are unknown. We examined two EMC with t(9;17)(q22;q11) and found that the CHN gene was recombined with the RBP56 gene from 17q11 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
31
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(32 citation statements)
references
References 26 publications
1
31
0
Order By: Relevance
“…Only one chondrosarcoma subtype, extraskeletal myxoid chondrosarcoma, is reportedly characterized by recurrent or specific chromosomal translocations. These translocations, the t(9;22)(q22; q12) or its variant, t(9;17)(q22;q11.2), result in the fusion of the CHN (TEC) gene at 9q22 with the EWS gene at 22q12 or the TAF2N (RBP56) gene at 17q11.2 (12)(13)(14)(15)(16)(17)(18).…”
Section: Discussionmentioning
confidence: 99%
“…Only one chondrosarcoma subtype, extraskeletal myxoid chondrosarcoma, is reportedly characterized by recurrent or specific chromosomal translocations. These translocations, the t(9;22)(q22; q12) or its variant, t(9;17)(q22;q11.2), result in the fusion of the CHN (TEC) gene at 9q22 with the EWS gene at 22q12 or the TAF2N (RBP56) gene at 17q11.2 (12)(13)(14)(15)(16)(17)(18).…”
Section: Discussionmentioning
confidence: 99%
“…The karyotypic complexity also varies widely, with some tumors showing a single numerical or structural chromosome aberration and others grossly rearranged karyotypes. Specific chromosomal changes have been noted only in extraskeletal myxoid chondrosarcomas (EMCs) that are characterized by t(9;22)(q22;q12) or, less often, t(9; 17)(q22;q11) and t(9;15)(q22;q21), resulting in the formation of the fusion genes EWS/CHN, RBP56/ CHN, and TCF12/CHN, respectively (Labelle et al, 1995;Stenman et al, 1995;Attwooll et al, 1999;Panagopoulos et al, 1999;Sjögren et al, 1999Sjögren et al, , 2000. Although nonrandom aberrations have been reported in other chondrosarcomas, no specific changes have been identified.…”
Section: Introductionmentioning
confidence: 99%
“…Recent cytogenetic and molecular studies have shown that EMC has recurrent chromosomal translocations such as t(9;22)(q22;q12) and t(9; 17)(q22;q11), resulting in fusions of the EWS and TAF2N (also called hTAFii68 or RBP56) genes to the NOR1 gene (also known as TEC, CHN, or MI-NOR), respectively (Clark et al, 1996;Brody et al, 1997;Attwooll et al, 1999;Labelle et al, 1999;Panagopoulos et al, 1999;Sjö gren et al, 1999). More recently, another type of chromosomal translocation, t(9;15)(q22;q21), generating a TCF12/ NOR1 fusion gene, has been identified in a case of a cellular-solid variant of EMC (Sjö gren et al, 2000).…”
mentioning
confidence: 97%